2020
DOI: 10.1002/pros.24084
|View full text |Cite
|
Sign up to set email alerts
|

Spine metastasis in patients with prostate cancer: Survival prognosis assessment

Abstract: Background: Patients presenting spine metastasis (SpM) from prostate cancer (PC) form a heterogeneous population, through this study, we aimed to clarify and update their prognostic assessment. Methods: The patient data used in this study was obtained from a French national multicenter database of patients treated for PC with SpM between 2014 and 2017. A total of 72 patients and 365 SpM cases were diagnosed. Results: The median overall survival time for all patients following the event of SpM was 28.8 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Moreover, bone metastasis is a significant milestone in the progression of prostate cancer and represents a systemic disease that greatly affects patient prognosis. Once bone metastasis occurs, prostate cancer patients may experience symptoms, such as bone pain, pathological fractures, and spinal cord compression, ultimately leading to a reduced quality of life and shortened lifespan [ 41 ]. Our findings indicated that PTHrP expression in tissues was significantly higher in phases M1b and M1c compared to phases M0 and M1a, implying that PTHrP may play a role in the bone metastasis process in clinical prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bone metastasis is a significant milestone in the progression of prostate cancer and represents a systemic disease that greatly affects patient prognosis. Once bone metastasis occurs, prostate cancer patients may experience symptoms, such as bone pain, pathological fractures, and spinal cord compression, ultimately leading to a reduced quality of life and shortened lifespan [ 41 ]. Our findings indicated that PTHrP expression in tissues was significantly higher in phases M1b and M1c compared to phases M0 and M1a, implying that PTHrP may play a role in the bone metastasis process in clinical prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of spine surgery for SSM on survival, several studies report that spine surgery provides the opportunity for patients to receive adjuvant therapy and thus may lead to improved survival [ 9 , 13 , 31 ]. However, these studies were also retrospective and included patients who received chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer will commonly metastasize to bone and OS in patients with spine metastases is roughly 2.5 years. 53 According to SEER, 7% patients diagnosed with prostate cancer have distant metastases at presentation, with 30.6% 5-year relative survival. 14 Androgen receptor antagonists including flutamide, bicalutamide and abiraterone are commonly used as first-line androgen deprivation agents resulting in improvement in patient outcomes; as reported by STAMPEDE trial median OS was not reached with addition of zoledronic acid, 81 months with addition of docetaxel, 76 months with addition of both, and 71 months with standard of care (Table 1).…”
Section: Prostate Cancermentioning
confidence: 99%
“…Prostate cancer will commonly metastasize to bone and OS in patients with spine metastases is roughly 2.5 years [ 53 ]. According to SEER, 7% patients diagnosed with prostate cancer have distant metastases at presentation, with 30.6% 5-year relative survival [ 14 ].…”
Section: Prostate Cancermentioning
confidence: 99%